La violence du bâtard dans deux romans d’Amérique centrale - Claire Pailler (Caravelle)
Born of unknown parents and left in the streets, or born of a peasant woman raped by the landlord’s son - the bastard is, according to Carlos Fuentes, an emblematic figure of the conquest of America; he carries a history of violence. By resorting to that violence himself, and perpetuating it within the family circle, the bastard, a central character in the two Central American novels studied here, seems the embodiment of a society based on injustice.